Defect-rich boron doped carbon nanotubes as an electrocatalyst for hybrid Li–air batteries. Issue 1 (2nd December 2021) - Wang, Yuyang; Yu, Mingfu; Zhang, Tianyu; Xue, Zhichao; Ma, Ying; Sun, Hong
Abstract : BC3 NTs with topological defects improve the performance of hybrid lithium–air batteries, conducive to the ORR and OER. Abstract : Carbon nanotubes (CNTs) have been used as a cathode material for hybrid Li–air batteries (HLABs); however, their catalytic abilities for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are relatively limited. Herein, to improve their catalytic performance, we have synthesized a boron-doped CNT (BC3 NT) with varying boron contents. The Raman spectrum proves that the more defects are due to the higher boron content. And HLABs based on BC3 NT show great cyclability and catalytic performance in air, with an overpotential value of 0.3 V for 200 hours at a current density of 0.05 mA cm −2 . Furthermore, theoretical calculations with density functional theory (DFT) confirm the effects of topological defects of BC3 NT on the ORR and OER. Since boron is doped into the CNT, BC3 NT containing a large amount of defect rings is obtained. And the generation of defects was conducive to the battery reaction. Accordingly, as a positive electrode material for HLABs, BC3 NT is more conducive to the ORR and OER, and the topological defect ring generated by it improved the ORR and OER performance.